2023
DOI: 10.1177/15459683231203194
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Nogo-A Antibody Therapy Improves Functional Outcome Following Traumatic Brain Injury

Brian E. Powers,
Son T. Ton,
Robert G. Farrer
et al.

Abstract: Background Traumatic brain injury (TBI) can cause sensorimotor deficits, and recovery is slow and incomplete. There are no effective pharmacological treatments for recovery from TBI, but research indicates potential for anti-Nogo-A antibody (Ab) therapy. This Ab neutralizes Nogo-A, an endogenous transmembrane protein that inhibits neuronal plasticity and regeneration. Objective We hypothesized that anti-Nogo-A Ab treatment following TBI results in disinhibited axonal growth from the contralesional cortex, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 116 publications
(136 reference statements)
0
0
0
Order By: Relevance
“…Tissue-engineered CS hydrogels have been demonstrated to promote neuroprotection, potentiate endogenous NSC renewal and mediate cellular and functional repair after sTBI [14,20,21]. Previous reports using rodent TBI models have suggested that the period between 4-5 weeks post-TBI constitutes a 'sub-acute' period after sTBI induction when animals first demonstrate sustained functional deficits [21][22][23]. Evidence also suggests that this timepoint is useful to determine treatment effects and differences between treated and untreated animal cohorts.…”
Section: Introductionmentioning
confidence: 99%
“…Tissue-engineered CS hydrogels have been demonstrated to promote neuroprotection, potentiate endogenous NSC renewal and mediate cellular and functional repair after sTBI [14,20,21]. Previous reports using rodent TBI models have suggested that the period between 4-5 weeks post-TBI constitutes a 'sub-acute' period after sTBI induction when animals first demonstrate sustained functional deficits [21][22][23]. Evidence also suggests that this timepoint is useful to determine treatment effects and differences between treated and untreated animal cohorts.…”
Section: Introductionmentioning
confidence: 99%